Framing Analysis of Anies Baswedan's Political Identity as an Innovative Campaign on TikTok - Rakatiwi, Yolandha; Sazali, Hasan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to explore the role of TikTok in Anies Baswedan's political campaign leading up to the 2024 presidential election. Employing a content analysis research method, the study focuses on innovative campaign messages and public interaction on the TikTok platform. The findings indicate robust community involvement and positive support, contributing to the enhancement of Anies' reputation. Strong branding was achieved through innovative campaign techniques, including the phrase “AMEN” and visual symbols such as white clothing and the one-finger gesture. This research underscores the significance of social media in contemporary Indonesian politics by demonstrating how TikTok shapes public perceptions of Anies Baswedan. By using TikTok as a central point of analysis, the study concludes that the platform has emerged as a crucial tool for innovative political communication and the cultivation of the public personas of future leaders.